Preliminarily report on molecular diversity of Sargassum species in Oman Sea by using ISSR and RAPD markers - Noormohammadi, Zahra; Baraki, Somaye Ghasemzadeh; Sheidai, Masoud (Acta Biologica Szegediensis, 2011)
Sargassum (Sargassaceae, Fucales) is a common macroalgal genus occurring throughout the world, except in the polar regions. Sargassum species are one of economically important brown algae in south of Iran. In this study, molecular variations were assessed in three Sargassum species; Sargassum tenerrimum J. Agardh, Sargassumglaucescens J. Agardh and Sargassum ilicifolium C.Agardh, widely distributed species in the southwest of Iran (Oman Sea). RAPD and ISSR markers were used to assess genetic variation within populations of each 3 species. Four of 30 RAPD primers as well as six combination of RAPD primers which have been used which all produced reproducible bands with high polymorphism (>96%). All populations in 3 species showed unique alleles which made unique profiles for each population. Twelve ISSR markers including single and combined primers showed high polymorphism (>94%). Nei’s genetic diversity, Shannon index showed high values between populations while no variations were observed within populations (Hpop =0, 1-Hpop/Hsp =1) in both molecular markers studied. AMOVA test also confirmed lack of variation within them. Different clustering like UPGMA and Neighbor Joining separated populations of each species studied based on RAPD and ISSR data. This is the first study on evaluation of inter-population variation in some of Sargassum species in Iran.